Bilingualism, Biliteracy, Biculturalism, and Critical Consciousness for All: Proposing a Fourth Fundamental Goal for Two-Way Dual Language Education. Issue 2 (3rd April 2019) - Palmer, Deborah K.; Cervantes-Soon, Claudia; Dorner, Lisa; Heiman, Daniel
Abstract : Two-way dual language (TWDL) bilingual education programs share three core goals: academic achievement, bilingualism and biliteracy, and sociocultural competence. This article proposes a fourth core goal: critical consciousness. Although TWDL programs are designed to integrate students from diverse language, culture, and race backgrounds, equity is unfortunately still a challenge in TWDL classrooms and schools. We argue that centering critical consciousness—or fostering among teachers, parents, and children an awareness of the structural oppression that surrounds us and a readiness to take action to correct it—can support increased equity and social justice in TWDL education. We elaborate four elements of critical consciousness: interrogating power, critical listening, historicizing schools, and embracing discomfort. We illustrate these elements with examples from TWDL research and practice. In addition, we describe how critical consciousness impacts and radicalizes the other three core goals, in turn supporting the development of more successful, equitable, and socially just TWDL schools.